Analysis of Graphene Field Effect Transistor Based Current Mirrors - Akkan, Nihat; Erkmen, Burcu (IEEE, 2016)
Current mirrors are important basic building blocks of analog electronic circuits. In this paper graphene field effect transistor (GFET) based basic and cascode current mirrors are studied. Drain current equations of the GFET model are coded with Verilog-A language and integrated to SPICE simulator. DC output characteristics of current mirror circuits are analyzed and compared for both configuration with the help of simulation results. AC analysis is also performed and frequency response of the circuits are observed. The simulation results show that GFET based current mirrors can operate properly, however there are some drawbacks to overcome.
Keywords: graphene; GFET; current mirrors; CIRCUIT; Engineering